(untitled) (Bangladesh Journal of Medical Science, 2014)
Objective: The aim of this routine to research (R to R) developmental study was to implement the Braden Scale (BS) to identify risks of pressure ulcer (PU) development among hospitalized patients with spinal cord injury admitted in National Institute of Traumatology and Orthopedic Rehabilitation (NITOR), Bangladesh. Methods: Rogers Diffusion of Innovation Theory and PU related literature were used to guide the development of the implementation. The subjects were 10 nurses and 13 doctors who were working at the NITOR. Different strategies were provided for the implementation of the BS including workshops to provide knowledge, persuasion, and decision making to implement the BS for the nurse participants. The outcomes of this study were to determine: (a) nurses adoption in terms of the rate of using the BS and the accuracy of using the BS to identify PU risks, (b) nurses satisfaction to use the BS, and (c) doctors satisfaction on the implication of the BS to identify the risks of PUs in hospitalized adult patients with paraplegia. Data were analyzed by descriptive statistics and percentage of agreement. Results: Weekly proportions of nurses adoption in terms of the rate of using the BS ranged from 96% to 100%. The accuracy of using the BS yielded percentage of agreement between 70.6% to 100% for each item of the BS. Nurses and doctors satisfactions were at very high levels. Mean score of nurses satisfaction was 98.5% (SD=1.23) and mean score of doctors satisfaction was 89.79% (SD=4.17). Conclusion: Nurses are capable to assess PU risks of paraplegic patients independently by using the BS and may be incorporated to identify PU risks in addition to their work protocol. After identifying the PU risks, effective nursing care should be implemented to the patients in order to prevent the PU formation. DOI: http://dx.doi.org/10.3329/bjms.v13i4.20587 Bangladesh Journal of Medical Science Vol.13(4) 2014 p.411-414